2015
DOI: 10.1098/rspb.2014.2879
|View full text |Cite
|
Sign up to set email alerts
|

On the evolution of dispersal via heterogeneity in spatial connectivity

Abstract: Dispersal has long been recognized as a mechanism that shapes many observed ecological and evolutionary processes. Thus, understanding the factors that promote its evolution remains a major goal in evolutionary ecology. Landscape connectivity may mediate the trade-off between the forces in favour of dispersal propensity (e.g. kin-competition, local extinction probability) and those against it (e.g. energetic or survival costs of dispersal). It remains, however, an open question how differing degrees of landsca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
33
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 66 publications
1
33
0
5
Order By: Relevance
“…This procedure avoids assuming boundary conditions for mutations and the associated biases. Selection on dispersal is an emergent phenomenon in our individual-based model, as fitness gains and losses are related to the landscape structure (Henriques-Silva et al 2015), kin competition (Hamilton and May 1977, Poethke et al 2007, Kubisch et al 2013 or dispersal costs (Bonte et al 2012), to name but three relevant selective agents.…”
Section: Individuals Inheritance and Evolutionary Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure avoids assuming boundary conditions for mutations and the associated biases. Selection on dispersal is an emergent phenomenon in our individual-based model, as fitness gains and losses are related to the landscape structure (Henriques-Silva et al 2015), kin competition (Hamilton and May 1977, Poethke et al 2007, Kubisch et al 2013 or dispersal costs (Bonte et al 2012), to name but three relevant selective agents.…”
Section: Individuals Inheritance and Evolutionary Dynamicsmentioning
confidence: 99%
“…Similarly, Nuismer et al (2003) and Gibert et al (2013), to name but two, show that the explicit spatial arrangement of coevolving populations (co-evolutionary hot-and coldspots) impacts coevolutionary dynamics and the maintenance of polymorphisms in antagonistic systems (for a detailed treatment of the geographic mosaic of coevolution see Thompson 2005). Recently, Muneepeerakul et al (2011) and Henriques-Silva et al (2015) have reported that network topology may even impact the evolution of dispersal kernels respectively density-dependent dispersal strategies in metapopulations. Recently, Muneepeerakul et al (2011) and Henriques-Silva et al (2015) have reported that network topology may even impact the evolution of dispersal kernels respectively density-dependent dispersal strategies in metapopulations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For simplicity, and to save computational time, we simulated asexually-reproducing organisms with a haploid unilocus system where phenotypic values were represented by the value of their unique allele (Kubisch et al 2014). Following previous models (Hovestadt et al 2010, Kubisch et al 2014, Henriques-Silva et al 2015, alleles from both traits (d and e opt ) inherited by the offspring had a small probability of mutation (m = 1 × 10 -3 ), in which a normallydistributed random number N (0, 0.04) was added to the allele's value.…”
Section: Individuals Genetics and Reproductionmentioning
confidence: 99%
“…Dispersal is a fundamental biological process that profoundly shapes the ecology and evolution of communities, and microbial communities are no exception (reviewed in Büchi and Vuilleumier , Henriques‐Silva et al. , Albright and Martiny ). Microbial dispersal is also key in models of disease dynamics and biocontrol, such as for wild and agricultural plant species (Alexandrova et al.…”
Section: Introductionmentioning
confidence: 99%